2017
DOI: 10.18632/oncotarget.16002
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the structure-activity relationship of leelamine necessary for inhibiting intracellular cholesterol transport

Abstract: Leelamine is an anticancer chemotherapeutic agent inhibiting intracellular cholesterol transport. Cell death mediated by leelamine occurs due to the lysosomotropic property of the compound, its accumulation in the lysosome, and inhibition of cholesterol transport leading to lack of availability for key processes required for functioning of cancer cells. The present study dissects the structure-activity-relationship of leelamine using synthesized derivatives of leelamine and abietic acid, a structurally similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Nanolipolee‐007 significantly induced intracellular cholesterol levels in both circulating and adherent C8161.Cl9‐vGFP (Figure c) and UACC 903M‐GFP (Figure d) cell lines compared to controls, while cotreatment with β‐cyclodextrin reversed the effect. This result suggested that cholesterol transport was inhibited in CTCs following Nanolipolee‐007 treatment and that it could be reversed using β‐cyclodextrin as reported in the literature (Gowda et al., ; Kuzu et al., , , ).…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Nanolipolee‐007 significantly induced intracellular cholesterol levels in both circulating and adherent C8161.Cl9‐vGFP (Figure c) and UACC 903M‐GFP (Figure d) cell lines compared to controls, while cotreatment with β‐cyclodextrin reversed the effect. This result suggested that cholesterol transport was inhibited in CTCs following Nanolipolee‐007 treatment and that it could be reversed using β‐cyclodextrin as reported in the literature (Gowda et al., ; Kuzu et al., , , ).…”
Section: Resultssupporting
confidence: 65%
“…β‐Cyclodextrin was premixed with melanoma cells to counteract Nanolipolee‐007, thereby demonstrating the involvement of cholesterol transport inhibition in mediating this process. Thus, leelamine killed circulating melanoma cells through a process that could be reversed using β‐cyclodextrin, which based on the literature, could be due to inhibition of cholesterol transport (Gowda et al., ; Kuzu, Toprak, Noory, & Robertson, ; Kuzu et al., , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Often, structure modeling tools are also used to design antibodies that target a specific epitope or to improve antigen binding of known antibodies . Moreover, several studies combined computational structure modeling and crystallographic approaches . Over the last years, antibody structure modeling has been developed to a level where it can also be used to gain information on antibody‐antigen interactions.…”
Section: Structure and Function Of Antibodiesmentioning
confidence: 99%